1992
DOI: 10.1002/kin.550241204
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation with permanganate in strong alkaline medium. Oxidation of pyruvic and lactic acids

Abstract: The reaction of permanganate ion with pyruvic acid and lactic acid has been studied in aqueous solutions containing 0.10-2.0 mol dm-3 alkali. In this range of HOconcentration the reaction 2Mn04 -+ Substrate -2Mn04 *-+ product is followed slowly by the reduction of manganate, thus, the above process can be studied separately. In the case of lactic acid (LA), the reactive species is alkoxy anion, and the deprotonation constant could be calculated from the kinetic data. A mechanism based on electron abstraction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…As it exhibits many oxidation states, the stoichiometric results and pH of the reaction media play an important role. Under the prevailing experimental conditions at pH >12, the reduction product of Mn(VII) is stable and further reduction of Mn(VI) might be stopped [7]. The Diode Array Rapid Scan Spectrophotometric (DARSS) studies have shown that at pH >12, the product of Mn(VII) is Mn(VI) and no further reduction was observed as reported by Simandi et al [13].…”
Section: Permanganate Ion Mno 4 )mentioning
confidence: 85%
See 2 more Smart Citations
“…As it exhibits many oxidation states, the stoichiometric results and pH of the reaction media play an important role. Under the prevailing experimental conditions at pH >12, the reduction product of Mn(VII) is stable and further reduction of Mn(VI) might be stopped [7]. The Diode Array Rapid Scan Spectrophotometric (DARSS) studies have shown that at pH >12, the product of Mn(VII) is Mn(VI) and no further reduction was observed as reported by Simandi et al [13].…”
Section: Permanganate Ion Mno 4 )mentioning
confidence: 85%
“…Furthermore, the mechanism by which this multivalent oxidant oxidises a substrate depends not only on the substrate but also on the medium [6] used for the study. In strongly alkaline medium, the stable reduction product [7] is the manganate ion, MnO 4 2) . No mechanistic information is available to distinguish between a direct one-electron reduction to Mn(VI) and a mechanism in which a hypomanganate is formed in a two-electron step followed by a rapid reaction [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more concentrated solution, the protonated form, V(OH) 3 2ϩ is more reactive. The observed increase in the reaction rate with the V(V) concentration varying from 0.50 ϫ 10 Ϫ2 to 2.50 ϫ 10…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation the addition of acrylamide to the reaction mixture has also been shown to yield the formation of a polymeric product indicating that V(V) behaves as an one-equivalent oxidant. Thus, these activated species, (X* 2ϩ ) and (Y* 2ϩ ), are decomposed to give the first CO 2 through a C 9 C fission producing a free radical, HOOCCH(OH)CH(OH)D, and V(IV) in the rate determining step, k 3 4.51 ϫ 10 mol s , sion, these results and the experimental rate laws show that the oxidation mechanism of tartaric acid involves different active species of vanadium(V) in sulfuric acid medium and depend on the ionic strength conditions of the experiments.…”
Section: ϫ2mentioning
confidence: 99%